Toxicological evaluation of germinated rough rice crude extract and its chemopreventive effects in inhibitting azoxymethane-induced abberant crypt foci formation in Sprague dawley rats - Saki, Elnaz (2015)
Rice is a nutritious staple food with health-promoting activity. Germination of rough rice (GRR) causes significant changes in several chemical compositions and bioactive compounds that might prevent or postpone the inception of cancer. This research was carried out to study the chemopreventive properties of GRR crude extract in Sprague dawley rats induced with azoxymethane. The antioxidant properties of GRR crude extract were determined by TPC, ABTS, DDPH and FRAP assays. The level of antioxidant activity of GRR crude extract as determined by TPC and FRAP assay was 105.75 and 69.16 (mg GAE/g GRR crude extract), respectively. The level of antioxidant activity of GRR crude extract as determined by ABTS and DDPH assay was 105.75 and 69.16 mg (Trolox Equivalent/g GRR crude extract), respectively. The correlation between antioxidant assays (ABTS, DDPH and FRAP) and total phenolic content was roughly high (R² = 0.9984) and showed the antioxidant property of GRR crude extract. The cytotoxic effect of GRR crude extract on HT29 cells after 72 hours was determined by MTT assay. IC50 value of GRR crude extract was 43 μg/mL. For the acute toxicity study of GRR crude extract, the OECD Guidelines 423 was followed. Forty male (6 weeks of age) Sprague dawley rats were divided in 4 groups (n=5) which were (G1) 2000 mg/kg body weight (GRR crude extract (g)/body weight of rat (kg)), (G2) 1500 mg/kg body weight, (G3) 500 mg/kg body weight and (G4) distilled water alone. GRR crude extract was administered orally one time per week for 14 days. No evidence of toxicity attributable to the treatment with GRR crude extract was observed based on the body and organ weight, hematological parameters and histological evaluation. The sub-acute toxicity study of GRR crude extract followed OECD Guidelines 407. Fifteen male Sprague dawley rats (6 weeks of age) were divided in to 4 groups (n=5) which were (G1) 2000 mg/kg body weight (GRR crude extract (g)/body weight of rat (kg)), (G2) 1000 mg/kg body weight, (G3) 500 mg/kg body weight and (G4) distilled water alone. GRR crude extract was administered orally one time daily for 8 weeks. No evidence of toxicity attributable to the treatment with GRR crude extract was observed based on the body and organ weight, hematological parameters and histological evaluation. For the chemopreventive properties of GRR crude extract, fifty male Sprague dawley rats (6 weeks of age) were randomly divided into 5 groups (n=10) which were (G1) positive control (with AOM, unfed with GRR crude extract), (G2) with AOM, fed with 2000 mg/kg body weight (GRR crude extract (g)/body weight of rat (kg)), (G3) with AOM, fed with 1000 mg/kg body weight, (G4) with AOM, fed with 500 mg/kg body weight and (G5) negative control (without AOM, unfed with GRR crude extract). In order to induce colon cancer, the rats received two intraperitoneal injection of azoxymethane (AOM) in saline (15 mg/kg body weight) for two subsequent weeks. Then, GRR crude extract was administrated orally once daily for eight weeks. Following the treatment, animals were sacrificed. Colons and all the organs (liver, kidney, lung, heart and spleen) were removed and weighed. Colonic aberrant crypt foci (ACF) were evaluated histopathologically. Treatment with 2000 mg/kg GRR crude extract gave the greatest reduction in the formation of ACF (p<0.05). From the histological classification of ACF, treatment with 2000 mg/kg GRR crude extract also had the highest percentage of non-dysplastic ACF. Expression of β-catenin was determined by Western blot analysis. The highest dose of GRR crude extract (2000 mg/kg (GRR crude extract (g)/ body weight of rat (kg)) showed the lowest level of β-catenin expression. In summary, GRR crude extract was not toxic to the animals and exhibited chemopreventive properties in rats induced with azoxymethane. GRR crude extract can be a promising dietary supplement component that might prevent or postpone the inception of cancer.